Vasodilation Effects of Ketapang (Terminalia catappa Linn) Fruit on Aortic Rings Rat - Wijaya, Joseffine Valentina; Ismail, Sjarif; Khotimah, Siti (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2024)
Hypertension is an important risk factor for cardiovascular disease. Hypertension requires long-term treatment to keep blood pressure under control. Exploration found that antihypertensive drugs have economic value. East Kalimantan is rich in medicinal plant diversity and needs to be explored to discover new drugs for hypertension. Ketapang fruit (Terminalia catappa Linn) has the potential to have a vasodilation effect so research is needed to explore vasodilation activity in vitro. This research to determine the vasodilation activity of Terminalia catappa fruit using isolated aortic ring bioassay. Twelve Wistar rats were used for bioassays isolated aortic ring with endothelium. The aortic rings is precontracted with phenylephrine. This study used two test groups, Control group and Terminalia catappa fruit ethanol extract group (FTC). The FTC and Control concentrations were given cumulatively in chamber of isolated aortic ring. Log concentration -2 FTC (-11.8 ± 3.5)% and Control (0.0 ± 0.0)%, p = 0,002; log concentration -1,5 FTC (-22.8 ± 2.5)% and Control (0.0 ± 0.0)%, p = 0,002; log concentration -1,0 FTC (-41.5 ± 2.8)% and Control (0.0 ± 0.0)%, p = 0,002; log concentration -0,5 FTC (-58.7 ± 3.1)% and Control (0.0 ± 0.0)%, p = 0,002; log concentration 0 FTC (-79.0 ± 3.4)% and Control (0.0 ± -1.9)%, p = 0,001; log concentration 0,5 FTC (-93.8 ± 3.0)% and Control (0.2 ± 1.5)%, p = 0,002. FTC causes vasodilation in isolated rat aortic rings with endothelium.